Examination of plant number and sowing date in different crop years - Máriás, Károly (Acta Agraria Debreceniensis, 2014)
We examinated three agrotechnical factors in 2011, 2012 and 2013 (sowing time, nutrient factor and plant density), as well as five different effects of genotypes on the crop of corn, on brown soil in the Hajdúság. The experiment was set next to the 47 main road in Debrecen, at the 6th kilometre stone. In the present processing I would like to touch on the effects of sowing time and plant density, as I do not have the chance to present the whole experiment results here. It is true for all three years that the humidity factors differ from the long years’ average, so the genotypes had different reactions on it. According to our results we found out that the late sowing time’s result had the most successful crop yield result with 9975 kg ha-1, while examining the plant density the result of the highest plant density proved to be the best with 9967 kg ha-1. We take the critical season in corns’ life cycle process into consideration when examining the results: June, July and August months’ humidity and temperature markers. According to the results in the tested 3 months we had 227 mm humidity with 10 days, when the average temperature was over 25 °C. The same factors in 2012 were 135.5 mm humidity with 37 days of average temperatures of 25 °C and in 2013 we recorded 102.5 mm humidity with 24 of these days. Our goal is to help the farmers in the Hajdúság with the results of our sowing times, hybrid choice and plant density results.